2017
DOI: 10.1002/term.2423
|View full text |Cite
|
Sign up to set email alerts
|

Tonsil‐derived mesenchymal stem cells (T‐MSCs) prevent Th17‐mediated autoimmune response via regulation of the programmed death‐1/programmed death ligand‐1 (PD‐1/PD‐L1) pathway

Abstract: Our knowledge of the immunomodulatory role of mesenchymal stem cells (MSCs) in both the innate and adaptive immune systems has dramatically expanded, providing great promise for treating various autoimmune diseases. However, the contribution of MSCs to Th17-dominant immune disease, such as psoriasis and its underlying mechanism remains elusive. In this study, we demonstrated that human palatine tonsil-derived MSCs (T-MSCs) constitutively express both the membrane-bound and soluble forms of programmed death-lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 32 publications
2
50
0
Order By: Relevance
“…MSCs produce cytokines and growth factors that contribute to recovery from injury by promoting cell proliferation, inhibiting apoptosis, regulating immune responses, and activating endogenous stem cells. Our research group has been using human palatine tonsil as a novel supply of MSCs, and the therapeutic effects of T-MSCs have been investigated in various mouse models of disease including psoriasis [17], BM ablation [18], osteoporosis [19], and liver cirrhosis [31]. Here, we demonstrate that T-MSC paracrine factors enhance BMT effectiveness and CM treatment alone could elicit these effects without the cells.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…MSCs produce cytokines and growth factors that contribute to recovery from injury by promoting cell proliferation, inhibiting apoptosis, regulating immune responses, and activating endogenous stem cells. Our research group has been using human palatine tonsil as a novel supply of MSCs, and the therapeutic effects of T-MSCs have been investigated in various mouse models of disease including psoriasis [17], BM ablation [18], osteoporosis [19], and liver cirrhosis [31]. Here, we demonstrate that T-MSC paracrine factors enhance BMT effectiveness and CM treatment alone could elicit these effects without the cells.…”
Section: Discussionmentioning
confidence: 84%
“…Previously, we demonstrated that human palatine tonsil-derived MSCs (T-MSCs) show tissue regenerative and immunomodulatory effects [15][16][17]. In addition, T-MSC infusion in allogeneic BM transplantation (BMT) and senile osteoporosis mouse models improved BM reconstitution [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, palatine tonsil tissue was also identified as a source of MSCs and tonsil-derived MSCs (T-MSCs) showed abundant expression of immunomodulatory proteins, compared with MSCs derived from the bone marrow and adipose tissue [15,16]. Moreover, studies for T-MSCs described an immunomodulatory effect on degenerative or inflammatory diseases [17][18][19][20]. Our previous study also demonstrated an immunomodulatory effect of T-MSCs in a mouse model of allergic rhinitis [21].…”
Section: Introductionmentioning
confidence: 92%
“…Some of these distinctive markers include CD106 (VCAM‐1) and CD274 (PD‐L1), and have functions in adhesion and migration as well as immunomodulation . In fact, there are numerous studies describing the immunomodulatory properties of TMSCs, most of which are involved in the general downregulation of inflammatory responses .…”
Section: Tonsil‐derived Mscs (Tmscs)mentioning
confidence: 99%
“…PD‐L1 of TMSCs prevents the differentiation of Th17, which is important for the inflammatory response of neutrophils and inflammatory disease . TMSCs can also hinder dendritic cell (DC) maturation and CD4+ T‐cell differentiation , while increasing IL‐10‐producing regulatory B‐cells to downregulate the inflammatory response .…”
Section: Tonsil‐derived Mscs (Tmscs)mentioning
confidence: 99%